2013
DOI: 10.1002/ppul.22866
|View full text |Cite
|
Sign up to set email alerts
|

Useful marker of oscillatory lung function in methacholine challenge test—comparison of reactance and resistance with dose–response slope

Abstract: The utility of the DRS_Xrs5 to differentiate asthmatics from controls was comparable to that of the DRS_FEV1 and better than that of the DRS_Rrs5 . In addition, IOS could detect additional asthmatic patients who did not show positive responses in spirometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…7 The usefulness of IOS in children has been well demonstrated and has even shown evidence of AHR in the absence of significant changes in spirometry. 8 This has allowed IOS parameters to be investigated as potential surrogate markers of AHR instead of spirometry in children. 9 Guidelines incorporate a standardized decrease in forced expiratory volume in 1 second (FEV 1 ) of 20% after bronchial provocation (PC 20 ) as evidence of AHR.…”
Section: Introductionmentioning
confidence: 99%
“…7 The usefulness of IOS in children has been well demonstrated and has even shown evidence of AHR in the absence of significant changes in spirometry. 8 This has allowed IOS parameters to be investigated as potential surrogate markers of AHR instead of spirometry in children. 9 Guidelines incorporate a standardized decrease in forced expiratory volume in 1 second (FEV 1 ) of 20% after bronchial provocation (PC 20 ) as evidence of AHR.…”
Section: Introductionmentioning
confidence: 99%
“…However, false negative or false positive results can occur in young children who cannot perform an acceptable manoeuvre. BHR has been assessed in young children using other methods including FOT, interrupter technique, whole-body plethysmography and transcutaneous oxygen measurement SPO 2 [ 5 , 47 , 60 - 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 However, changes in IOS parameters are well correlated with those in FEV 1 in many studies. 7,14,23 As shown in our previous studies, we investigated which IOS parameter is more correlated with BHR and found that reactance better reflects BHR than resistance. We do not have clear explanation for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although bronchial hyperresponsiveness is usually confirmed by measuring PC 20 _FEV 1 , the provocative concentration causing a 20% fall in FEV 1 by spirometry, 21 we were not able to calculate PC 20 _FEV 1 accurately as FEV 1 was performed only at baseline and at the last step and described as dichotomy of positive or negative results. We therefore used the dose-response slope, 22,23 PC 80 _Xrs 5 8,23,24 and PC 40 _Rrs 5 14,25,26 to compare bronchial hyperresponsiveness in our EOT + and EOT − groups. PC 80 _Xrs 5 and PC 40 _Rrs 5 positive means that the rate of change in the last step from baseline decreased by 80% or more in reactance and increased by 40% or more in resistance when measuring with IOS.…”
Section: Calculation Of Cumulative Dose Of Methacholinementioning
confidence: 99%
See 1 more Smart Citation